Leveraging digital absorptive capacity to promote sustainable development of Small and Medium-sized Enterprises in the manufacturing sector in Vietnam - Kim Hương Trang; Đinh Văn Hoàng; Nguyễn Hồng Vân; Nguyễn Hữu Thịnh (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kinh tế và Quản trị kinh doanh)
The study focuses on analyzing the impact of digital absorptive capacity on the sustainability of Small and Medium-sized Enterprises (SMEs) in the manufacturing industry in Vietnam. The study is based on the theoretical foundation of knowledge absorptive capacity (Cohen & Levinthal, 1990) combined with the perspective of sustainable development (Dyllick & Hockerts, 2002). Through a survey of 377 manufacturing SMEs in Vietnam and the application of Partial Least Squares Structural Equation analysis (PLS-SEM ), the results indicate a positive correlation between digital absorptive capacity and the sustainable development of enterprises. However, the analysis does not find a moderating effect of digital leadership in this relationship. The findings from the study not only shed light on the importance of improving digital absorptive capacity but also propose practical solutions to help manufacturing SMEs in Vietnam develop sustainably.